Pengaruh Transformasional Leadership Terhadap Employee Performance yang Dimediasi oleh Organization Citizen Behavior (OCB) dan Work Motivation pada Pegawai Kantor Kecamatan Jepara - Rahmawati Hadiastutik; Joko Utomo; Supriyono Supriyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research analysis the influence of Transformational Leadership on Employee Performance mediated by Organizational Citizenship Behavior (OCB) and Work Motivation on employees of the Jepara District Office. The study uses a quantitative approach with a causality survey method. The study population includes all employees of the Jepara District Office with a total sampling technique. Data collection was carried out through questionnaires and analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 3 software. The results of the research indicate that Transformational Leadership has a positive and significant effect on OCB and Work Motivation. Work Motivation has a positive and significant effect on Employee Performance and is proven to mediate the relationship between Transformational Leadership and Employee Performance. Conversely, OCB has no significant effect on Employee Performance and cannot act as a mediating variable. The research model indicates that Employee Performance can be explained by 68.8% of the variables in the model. This research concludes that improving employee performance is more effective through strengthening work motivation supported by transformational leadership than through extra-role behavior (OCB).